“Dosis de fertilización granulando a base de micro elementos en el rendimiento de grano seco del frijol trepador (phaseolus vulgaris) variedad huasca ´poroto en el distrito de Lamas” - García Luna, Roberto Carlos (2015)
This research paper entitled "Dose of fertilizer granules Sased Micro Elements in Grain Yield Dry Sean Climber (Phaseolus vulgaris) Sean Variety Huasca the District of Lamas", was conducted in order to evaluate the effect tour doses of granular micro efements based on the yield of dry grain climbing bean variety Huasca Poroto fertilizer and performing economic analysis of treatments. The statistical design of randomized complete block design (RCSD) with three repetitions and tour treatments was used. The results indicate that with the application of 100 kg I ha-1 (T4) of granulated fertilizer based on microelements higher average yields, seed weight, plant height and number of pods per plant were obtained with 6 799.2 kg ha-1, 0.5 g, 2.02 m and 154.8 pods per plant respectively, statistically beating the averages of the other treatments, followed by T3 (75 kg I ha-1), T2 (50 kg I HA 1), T1 (25 kg I ha-1) and TO (control). The T4 (100 kg I ha-1) treatment had the highest value of SIC with 1.59 anda net profit of S /. 3773.88 nuevos soles, followed by T3 (75 kg I ha-1), who obtained a value of B I C of 1.33 with net profrt of SI .2424.02 soles. T2 (50 kg I ha- 1), T1 (25 kg I ha-1) and TO (control) treatments obtained a value of B I C with 0.87, 0.52 and 0.21 respectively, and negativa net profit of S l. -909.12, -3018.10 And - 4674.46 soles respectively. Keywords: effect, doses, Micro elements, beans, trellis, analysis, economic, seed pod weight.